Crisis in Kazakhstan: The hollow core of Eurasia’s most “stable” autocracy exposed - Silvan Kristiina; Ketola Johanna (Ulkopoliittinen instituutti, 2026)
What started as a peaceful protest over commodity prices escalated into a mass display of popular dissatisfaction and a clash within the ruling elite. While President Kassym-Jomart Tokayev seems to have come out on top in the unexpected crisis, the impact of January 2022 will be profound and long-lasting in Kazakhstan and the region as a whole.